Verificação dos empreendimentos e a análise do perfil dos empreendedores do município de José da Penha – RN - Dantas, Heverton Azevedo (Universidade Federal Rural do Semi-Árido, 2020)
In the world scenario, there is a large index of entrepreneurs, in Brazil this index is increasing more and more, and in Rio Grande do Norte there is a strong concentration of it, because entrepreneurship is a very important element for the development of the also bringing social inclusion, job and income generation. Therefore, a project was created in order to analyze the entrepreneurial characteristics and the character of the entrepreneurs of the municipalities of that state. In this sense, this work shows a research done in the city of José da Penha-RN, which aims to verify the enterprises and the analysis of the profile of the entrepreneurs in that region. Thus, from this research it will be possible to highlight the lack and opportunities that it has. In the field research, a questionnaire was made with objective and discursive questions with the interest of assessing the distribution by gender, the age group of the entrepreneurs, education, the company profile, how many enterprises are registered, number of employees, the size of the company, the use of technology within the company, and how the projects are disclosed, I will show the causes that led the individual to undertake, and the main difficulties faced in their daily lives. This work is extremely important for new entrepreneurs who are thinking of opening their own business in the city of José de Penha, making them create a means to reverse these difficulties.
Keywords: Empreendedor; Empreendedorismo; José da Penha-RN; Entrepreneur; Entrepreneurship; José da Penha-RN; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA